Organizational Form and Performance: Evidence from the Hotel Industry - Kosová, Renáta; Lafontaine, Francine; Perrigot, Rozenn (The Review of Economics and Statistics, 2013)
We use a unique proprietary panel data set from a large hotel company to study how organizational form affects hotel pricing and performance. Aggregate data patterns suggest sizable performance differences between franchised and company-operated hotels. However, after controlling for other factors, we find that if significant at all, such differences are economically small. Moreover, once we endogenize the choice of organizational form, the differences become insignificant. We conclude that the company chooses which hotels to franchise and operate corporately such that, conditional on hotel and market characteristics, it obtains consistent outcomes across organizational forms.